Educadores Sociais nos municípios das Regiões Metropolitanas do Paraná: um olhar sob a perspectiva da Pedagogia Social Comparada (2009-2019) - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
The aim of this dissertation is to analyze the criteria used by the public notices for the recruitment of Social Educators in the Metropolitan Regions of the state of Parana. The sources used include information made available in public notices of municipal public contests in the eight Metropolitan regions of the state in the period from 2009 and 2019. This research is supported by Pierre Bourdieu’s field theory, mainly the concepts of habitus, field, capital and strategy, as well as on the Comparative Social Pedagogy and is divided into three chapters. The first comprises the theoretical background, since it addresses Bourdieu’s field theory and specifically the methodology, privileging a description of the process of location, selection and form of analysis of the data referring to the public notices of contests in a dialogical relation with the Comparative Social Pedagogy. The second chapter proposes the discussion of Social Pedagogy and Social Education as research and professional fields, from a historical approach. It also refers to the positions and positioning of Social Educators in the political horizon of recognition of these areas. Finally, the third chapter problematizes the organization and structure of the public notices advertising public contests, by systematizing an analytical framework from three categories, namely, terminology and attributions; qualification and requirements; workload and salary. In specific terms, it is possible to state that: 1) in 49.19% of the public notices the terminology Social Educator appears and in 51.81% of the notices found, other terms are used to refer to the professional activity. 2) in 14.75% of the cases, higher education is required, 1.63% accept incomplete higher education, 3.27% require elementary education, while 24.59% demand high school education in some specific courses, and 55.73% require only high school education. 3) there is discrepancy regarding salaries, that is, between municipalities of the same regions and between metropolitan regions, different salaries are offered. In general, the analysis allowed the evaluation of the permanence of habitus constituted throughout the Social Education history, but also enabled the observation of certain rupture. On the one side, the fact that a single specific term is not used to refer to the professional of this area, as well as the ambiguity regarding the minimum education required, the inexistence of a Social Education academic course and the discrepancy related to salaries paid, reinforce a view that this type of work still holds some relation with the old welfare, compensatory and voluntarist view. On the other hand, the fact that significant part of the public notices calls these professionals Social Educators, some require higher education qualification and offer a better salary according to their level of education, reveals the incorporation of the idea of a Social Education marked by the principles of Human Rights that are present in the 1988 Brazilian Constitution, the Statute of the Child and Adolescent, as well as by specific norms destined to the elderly, quilombolas, and indigenous populations. Finally, when confronting the data from the public notices with the Social Education and Social Pedagogy history, it is possible to affirm that the process of recruitment of Social Educators in the municipalities under analysis keeps some relation with the debates and disputes that occur in this area and the struggles of the social world.
Keywords: Educadores Sociais; Educação Social; Pedagogia Social Comparada; Habitus; Campo; Social Educators; Social Education; Comparative Social Pedagogy; Habitus; Field; CNPQ::CIENCIAS HUMANAS::EDUCACAO